Integrative Single-Cell RNA-Seq and ATAC-Seq Analysis of Mesenchymal Stem/Stromal Cells Derived from Human Placenta - Li, Jinlu; Wang, Quanlei; An, Yanru; Chen, Xiaoyan; Xing, Yanan; Deng, Qiuting; Li, Zelong; Wang, Shengpeng; Dai, Xi; Liang, Ning; Hou, Yong; Yang, Huanming; et al. (Frontiers in Cell and Developmental Biology, 2022)
Mesenchymal stem/stromal cells derived from placenta (PMSCs) are an attractive source for regenerative medicine because of their multi-differentiation potential and immunomodulatory capabilities. However, the cellular and molecular heterogeneity of PMSCs has not been fully characterized. Here, we applied single-cell RNA sequencing (scRNA-seq) and single-cell assay for transposase-accessible chromatin sequencing (scATAC-seq) to cultured PMSCs from human full-term placenta. Based on the inferred characteristics of cell clusters, we identified distinct PMSC subsets, including immunomodulatory-potential population with high expression of immunoregulatory molecules and highly proliferative subpopulations. Further, integrative analysis of gene expression and chromatin accessibility inferred more significant chromatin accessibility than transcription on immunomodulatory-related genes. Cell cycle gene-related heterogeneity has more significant characteristics at the transcriptional level than chromatin accessible level in PMSCs. We further revealed putative subset-specific cis-regulatory elements regulating the expression of immunomodulatory-related genes and proliferating-related genes in immunomodulatory-potential and proliferating subpopulation, respectively. Moreover, we inferred a novel transcription factor PRDM1 might play a crucial role in maintaining immunomodulatory capability by activating PRDM1-regulon loop. Collectively, our research first provides a comprehensive and integrative study of the transcriptomic and epigenomic features of PMSCs, which paves the way for a deeper understanding of cellular heterogeneity and offers fundamental biological insight of PMSCs subsets-based cell therapy.